Given:
The function is:
[tex]f(x)=x[/tex]
The graph of this function reflected across the x-axis. The graph is then translated 11 units up and 7 units to the left.
To find:
The equation of the transformed function.
Solution:
The translation is defined as
[tex]g(x)=kf(x+a)+b[/tex] .... (i)
Where, k is stretch factor, a is horizontal shift and b is vertical shift.
If 0<k<1, then the graph compressed vertically by factor k and if k>1, then the graph stretch vertically by factor k.
If k<0, then the graph is reflected across the x-axis.
If a>0, then the graph shifts a units left and if a<0, then the graph shifts a units right.
If b>0, then the graph shifts b units up and if b<0, then the graph shifts b units down.
The graph of this function reflected across the x-axis. The graph is then translated 11 units up and 7 units to the left. So, [tex]k=-1, b=11, a=7[/tex]. Putting these value in (i), we get
[tex]g(x)=(-1)f(x+7)+11[/tex]
[tex]g(x)=-(x+7)+11[/tex] [tex][\because f(x)=x][/tex]
[tex]g(x)=-x-7+11[/tex]
[tex]g(x)=-x+4[/tex]
Therefore, the required function is [tex]g(x)=-x+4[/tex].